EVALUASI KINERJA PELAYANAN JALAN KOTA TEMBILAHAN KABUPATEN INDRAGIRI HILIR (Studi Kasus Jalan H. Arief Tembilahan Kota) - Haris Swandi , Akbar Alfa (Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir Riau, 2019)
Transportation is a part that is not separate from urban planning. Urban planning without considering the conditions and patterns of transportation that will occur as a result of the plan itself will bring about the consequences of a long chain with increasing transportation problems. The main function of a road based on MKJI 1997 is to provide transportation services so that road users can drive safely and comfortably. The parameters of traffic flow that are important factors in traffic planning are traffic volume, speed and density. The traffic volume on the H. Arief Tembilahan road exceeds the capacity value, where the value of vehicle traffic volume for 2019 is 3568 smp / hour, and the planned traffic volume calculated by the traffic flow prediction method for the next 10 years is 1354.74 smp / hour.